The Correlations Between Dietary Patterns and Compliance with Iron–Folic Acid (IFA) Supplementation and The Incidence of Anemia - Yusran, Muhammad; Farhat, Yasir; Pratiwi, Niken; Nurhamidi (Jurusan Gizi Poltekkes Kemenkes Banjarmasin, 2026)
Anemia among adolescent girls remains a public health problem in Indonesia. The Indonesian Health Survey (SKI) 2023 reported anemia prevalence of 16.3% among those aged 5–14 years and 15.5% among those aged 15–24 years. In South Kalimantan Province, anemia prevalence reached 52.98%, while in Pandawanan Village it was 51.85%. This study aimed to examine the relationship between dietary patterns and compliance with iron tablet consumption and the incidence of anemia among adolescent girls in Pandawanan Village, within the working area of UPT Puskesmas Guntung. A cross-sectional design was used with a total sample of 36 adolescent girls. Data were collected through hemoglobin measurement, assessment of dietary patterns using a Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ), and a Health Belief Model–based questionnaire on TTD compliance. Data were analyzed using the Spearman rank correlation test. The prevalence of anemia was 72.22%. Significant relationships were found between dietary patterns and anemia (p = 0.001; r = 0.689) and between TTD compliance and anemia (p = 0.038; r = –0.347). Poor dietary patterns and low compliance were associated with a higher risk of anemia.